Morphometric patterns in Recent and fossil penguins (Aves, Sphenisciformes) - Livezey, Bradley C. (J Zool (1987), 2009)
A total of 622 skin specimens, 527 skeletons, and myological data compiled by Schreiweis (1972) were used to investigate morphometric patterns within and among the 18 Recent species of Spheniscidae, and to compare the family with a fighted species, the common diving‐petrel (Pelecanoides urinator), considered by some authorities to be similar to the flighted ancestor of penguins. Fossil penguins also were studied using measurements from 111 skeletal elements representing 18 species. Most external and skeletal measurements follow interspecific rankings in body mass; the latter span a 30‐fold range from 1 kg in Eudyptula minor to 30 kg in Aptenodytes forsteri. Flighted Pelecanoides is only one‐tenth the mass of the smallest spheniscid. Wing areas and body masses of penguins maintain approximate geometric similitude among species; the allometric coefficient is 0.62 ± 0.04. Several skeletal elements are less derived in conformation in the fossil penguins than in modern confamilials. Despite great variation in the lengths of wing and leg skeletons, penguins show relative consistency in proportions of wing elements; pelvic proportions were more variable within the Spheniscidae. Proportions within both limbs are distinctly different from those of Pelecanoides. Analysis of correlation structures within species of penguin revealed three major subsets of skeletal variables that are highly intercorrelated: trunk‐skull lengths, appendicular‐trunk widths, and appendicular lengths. Within these groups, measurements tend to separate by anatomical region and, to a lesser degree, by limb. Canonical analysis of skin and skeletal measurements revealed groupings of spheniscids on the basis of size and relatively complex shape variables. Cluster analyses of taxa on the canonical variates confirmed the similarity of congeners in Eudyptes, Eudyptula and Spheniscus; species of Aptenodytes and, to a lesser degree, Pygoscelis, are more heterogeneous. A cluster analysis of principal components of myological measurements tabulated by Schreiweis (1972) corresponded closely with phenetic groupings using external and skeletal variables. A canonical contrast between spheniscids and Pelecanoides indicated that the families differ in a relatively complex skeletal dimension that only in part reflects overall size. Multivariate assessment of sexual dimorphism in external and skeletal variables indicated that: Eudyptula is least dimorphic; Aptenodytes, Eudyptes, Megadyptes and Spheniscus are moderately dimorphic; and Pygoscelis is most dimorphic. Pelecanoides shows comparatively low dimorphism. Among‐species and within‐species first principal components of skeletal measurements (multivariate axes of skeletal ‘size’) differ from one another in their orientation, and both deviate from isometric size. The first principal component for skeletons of Pelecanoides also deviated from isometric size, but the direction of this allometry is fundamentally different from that in penguins. Estimates of body mass for fossil penguins, based on principal components of available skeletal measurements, indicate that fossil species ranged from 3 kg to 81 kg in total mass; the largest fossil species was approximately 2.5 times as massive as the largest extant spheniscid. Much of the morphometric variation in the Spheniscidae is explainable on locomotory, ecological and thermodynamic grounds, and the associated phenetic groupings conform broadly with traditional generic classifications. The evolutionary significance of mensural correlations, allometric trends and differences between fossil and Recent species are discussed, and the need for a phylogenetic analysis of this highly specialized family of winged‐propelled diving birds is stressed.